(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nanomaterials have elevated the importance of science and innovation. Their advancement has substantial impact on a wide range of applications, from catalysis to electronics data storage. Properties and synthesis of different kinds of nanomaterials are also reviewed with special emphasis on the semiconductor-noble metal and noble metal–noble metal hybrid nanomaterials. Variation of properties of nanomaterials with the modification of shape, size and dimension is also described along with their potential field of applications in this part. This article will serve as initial point for the development of noble metal nanomaterials, which will bring new possibilities in nanocatalysis.